Against intellectual monopoly - Boldrin, Michele 1956- (Cambridge University Press, 2008)
'Intellectual property' - patents and copyrights - have become controversial. We witness teenagers being sued for 'pirating' music - and we observe AIDS patients in Africa dying due to lack of ability to pay for drugs that are high priced to satisfy patent holders. Are patents and copyrights essential to thriving creation and innovation - do we need them so that we all may enjoy fine music and good health? Across time and space the resounding answer is: No. So-called intellectual property is in fact an 'intellectual monopoly' that hinders rather than helps the competitive free market regime that has delivered wealth and innovation to our doorsteps. This book has broad coverage of both copyrights and patents and is designed for a general audience, focusing on simple examples. The authors conclude that the only sensible policy to follow is to eliminate the patents and copyright systems as they currently exist
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Intellectual property / Economic aspects; Competition; Monopolies; Intellectual property -- Economic aspects; Urheberrecht; Marktwirtschaft; Innovationswettbewerb; Geistiges Eigentum; Monopolmissbrauch; Patentschutz